High correlation between net promoter score and the development of consumers' willingness to pay (Empirical evidence from European mobile markets) - François Jeanjean (International Telecommunications Society (ITS), 2011)
This paper shows that the correlation between the Net Promoter Score and consumers' Willingness To Pay in five European mobile markets is very strong. The Net Promoter Score is provided by a survey and the Willingness To Pay is calculated using the Spokes Model which is an economic model based on horizontal differentiation among firms. The model input data (firms' revenues, number of subscribers and profits) are provided by Merill Lynch, Bank of America. The well-known correlation between Net Promoter Score and Revenues is weaker and arises from the previous correlation. The same is true of the correlation between Net Promoter Score and Profits.
Keywords: D11; D43; L13; L96; M31; 330; Net Promoter Score; recommend intention; customer satisfaction; consumer's Willingness to Pay